2005
DOI: 10.1007/s00784-005-0020-5
|View full text |Cite
|
Sign up to set email alerts
|

Roots of the maxillary first and second molars in horizontal relation to alveolar cortical plates and maxillary sinus: computed tomography assessment for infection spread

Abstract: The purposes of this study were to investigate the horizontal relationship of the roots of maxillary molars with the cortical plates and the maxillary sinus and to investigate the influence of these relationships on the spread of odontogenic infection. Computed tomography images of 120 control subjects and 49 patients with infection originating in the maxillary first or second molar were investigated. In the control group, more than 60% of the first molar roots contacted both palatal and buccal cortical plates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
42
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 13 publications
8
42
0
5
Order By: Relevance
“…La fréquence plus faible des cellulites à point de départ maxillaire tient à la profondeur du vestibule et à la pauvreté Tableau I. Répartition des cas en fonction de la dent causale. en tissu cellulo-graisseux, notamment du côté du palais où la fibro-muqueuse adhérente limite la propagation de l'infection entraînant seulement la formation d'un abcès sous-périosté [12,15,16]. À la mandibule, la relation entre le site de fenestration osseuse et la molaire mandibulaire causale est significative.…”
Section: Discussionunclassified
“…La fréquence plus faible des cellulites à point de départ maxillaire tient à la profondeur du vestibule et à la pauvreté Tableau I. Répartition des cas en fonction de la dent causale. en tissu cellulo-graisseux, notamment du côté du palais où la fibro-muqueuse adhérente limite la propagation de l'infection entraînant seulement la formation d'un abcès sous-périosté [12,15,16]. À la mandibule, la relation entre le site de fenestration osseuse et la molaire mandibulaire causale est significative.…”
Section: Discussionunclassified
“…Furthermore, periradicular and periodontal pathoses originating from posterior maxillary teeth may spread into the maxillary sinus (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Therefore, recent studies have focused on using CT (4,12,13) or cone-beam computed tomographic (CBCT) imaging (14)(15)(16)(17)(18) for assessing the proximity between the roots and the sinus floor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, it has been shown in surveys, that up to 95% of dentists refer their patients solely for an OPG scan before implant placement with only a relatively small number of referrals for a CT scan [10,11]. It is interesting to know, that several studies assessed the vertical and horizontal relationship between the tooth root apex and the inferior wall of the maxillary sinus using CT diagnostic method [12][13][14][15][16]. It was concluded that CT is more accurate than OPG in assessing the tooth root and sinus relationship [17].…”
Section: Introductionmentioning
confidence: 99%